Dual-cavity spectrometer for monitoring broadband light extinction by atmospheric aerosols. Issue 10 (2nd October 2020) - Saseendran, Aiswarya; Mathai, Susan; Joshi, Shreya; Pakkattil, Anoop; Capek, Tyler; Kinney, Gregory; Mazzoleni, Claudio; Varma, Ravi
Abstract: Atmospheric Aerosols affect Earth's climate directly by scattering and absorbing solar radiation. In order to study the optical properties of aerosols, we developed a broadband cavity-enhanced spectrometer that uses a supercontinuum laser source and a compact spectrometer, to measure simultaneously the extinction coefficient of aerosols over a broad wavelength region from 420 to 540 nm. The system employs a dual cavity approach with a reference and a sample cavity, accounting for changes in gases background and for laser spectral and intensity fluctuations. We tested the system with aerosolized salt particles and polystyrene latex spheres. We performed calculations using Mie theory and found good agreement with the measured extinction. We also found that the extinction coefficient of non-absorbing aerosol favorably compares with the scattering coefficient measured by a nephelometer. Finally, we generated soot particles and found an extinction Ångström exponent in good agreement with values reported in the literature. Wavelength dependent detection limits (1 σ ) for the instrument at 5 nm wavelength resolution and for an integration time of ∼10 min were found to be in the range ∼5 Mm −1 to 13 Mm −1 . The broadband dual-cavity extinction spectrometer is simple and robust and might be particularly useful for laboratory measurements of the extinction coefficient of brown carbon aerosol. The laboratory tests suggest that the prototype is promising for future developments of a field-deployable instrument. Copyright © 2020 American Association for Aerosol Research